A Preliminary Study of Voluntary Cough Motor Performance and Learning With Skill Training and Biofeedback. - Borders, James C.; Lowell, Emilie R.; Huber, Jessica E.; Quinn, Lori; Troche, Michelle S. (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Sensorimotor cough skill training (CST) has been shown to improve cough strength, as well as facilitate changes during training (i.e., motor performance) and generalization to untrained tasks (i.e., motor learning). However, there is a gap in our understanding of the effects of voluntary CST (without sensory stimuli) on motor performance and learning. Furthermore, the contribution of physiologic factors, such as lung volume, a driver of cough strength in healthy adults, and treatment-specific factors, such as biofeedback, remains unexamined. Method: Twenty individuals with Parkinson’s disease (PD) completed pre- and post-CST single voluntary, sequential voluntary, and reflex cough testing. Participants were randomized to biofeedback or no biofeedback groups. They completed one CST session involving 25 trials of voluntary coughs, with the treatment target set 25% above baseline peak flow. Participants were instructed to “cough hard” to exceed the target. In the biofeedback group, participants received direct visualization of the target line in real time. Results: Cough peak flow showed positive improvements in motor performance (β = .02; 95% credible interval [CI]: 0.01, 0.03) and learning (β = .26; 95% CI: 0.03, 0.47). Changes in lung volume from pre- to post-CST did not predict treatment response. No differences in treatment response were detected between the biofeedback groups. Conclusions: A single session of voluntary CST improved voluntary cough motor performance and learning. Although lung volume increased during CST, changes to lung volume did not predict treatment response. These findings demonstrate the potential of voluntary CST to improve motor performance and motor learning among individuals with PD and cough dysfunction.